Sol-gel-derived calcium silicate cement incorporating collagen and mesoporous bioglass nanoparticles for dental pulp therapy - Simila, Hazel; Anselmi, Caroline; Cardoso, Lais M.; Dal-Fabbro, Renan; Beltrán, Ana M.; Bottino, Marco C.; Boccaccini, Aldo R. (Dental Materials, 2024)
Objective: Calcium silicate cements (CSCs) are often used in endodontics despite some limitations related to their physical properties and antibacterial efficacy. This study aimed to develop and demonstrate the viability of a series of CSCs that were produced by sol-gel method and further modified with mesoporous bioactive glass nanoparticles (MBGNs) and collagen, for endodontic therapy. Methods: Calcium silicate (CS) particles and MBGNs were synthesized by the sol-gel method, and their elemental, molecular, and physical microstructure was characterized. Three CSCs were developed by mixing the CS with distilled water (CS+H2O), 10 mg/mL collagen solution (CS+colH2O), and MBGNs (10 %) (CSmbgn+colH2O). The mixing (MT) and setting (ST) times of the CSCs were determined, while the setting reaction was monitored in real-time. Antibacterial efficacy against Enterococcus faecalis (E. faecalis) and regenerative potential on dental pulp stem cells (DPSCs) were also analyzed. Results: The CS+H2O displayed a ST comparable to commercial products, while CSmbgn+colH2O achieved the longest MT of 68 s and the shortest ST of 8 min. All the experimental CSCs inhibited the growth of E. faecalis. Additionally, compared to the control group, CSCs supported cell proliferation and spreading and mineralized matrix production, regardless of their composition. Significance: Tested CSCs presented potential as candidates for pulp therapy procedures. Future research should investigate the pulp regeneration mechanisms alongside rigorous antibacterial evaluations, preferably with multi-organism biofilms, executed over extended periods.
CRIS-Team Scopus Importer:2024-09-06
Keywords: Anti-bacterial agents; Calcium silicate; Collagen; Dental pulp; Mesoporous bioactive glass nanoparticles; Odontogenic